Median Nerve-Neurophysiological Index Correlates With the Survival of Patients With Amyotrophic Lateral Sclerosis - Xu, Liu-Qing; Hu, Wei; Guo, Qi-Fu; Lai, Lu-Lu; Xu, Guo-Rong; Chen, Wan-Jin; Wang, Ning; Zhang, Qi-Jie (Frontiers in Neurology, 2020)
Objective: This study aims to explore the association between median nerve-neurophysiological index (NI) and survival of patients with amyotrophic lateral sclerosis (ALS). Methods: A retrospective case series with a prospective follow-up study was performed in 238 patients with ALS. Their clinical profiles and NI were recorded. Kaplan-Meier curves and Cox regression were adopted to perform survival analysis. Results: The median survival time of all ALS cases was 33.0 months. Multivariate analysis showed that older age of onset, shorter diagnostic delay, higher ΔALSFRS-R, and faster progression {NI ≤ 2.15; hazard ratio [HR] = 1.543 [95% confidence interval (CI), 1.136–2.094]} were associated with short survival. NI was correlated with ALSFRS-R at baseline (rs = 0.3153; p < 0.0001) and ALSFRS-R at different time points of follow-up (rs = 0.5127; p < 0.0001). The higher NI slope of decline (> 0.25) showed shorter survival compared with the lower group (≤ 0.25; 34.0 vs. 52.0 months; p = 0.0003). A predictive model was constructed based on the age of onset, diagnostic delay, median nerve NI, and ΔALSFRS-R. The higher predictive score (> 14) showed significantly shorter survival compared with the lower group (≤ 14; HR = 3.907, 95% CI, 2.857–5.342). Conclusion: Median nerve NI and its slope of decline were predictive of survival of ALS.